“SparkTrack” Tracking Cleaning Progress - Vyshhnavi a/p Selvarajan; Novia Madeline a/p Michael; Fareeza Nurzafira Khairul Nizam; Kassim, Noordiana (Multidisciplinary Applied Research and Innovation, 2026)
Maintaining proper restroom cleanliness is crucial for ensuring hygiene and comfort in heavily frequented areas, particularly university campuses. Traditional management approaches for restroom maintenance is generally dependent on manual reporting mechanisms and rigid cleaning schedules. It is unfortunate that, this frequently results in maintenance delays, inconsistent campus cleanliness standards, and a lack of realtime monitoring capabilities. This project aims to develop a mobile application called "SparkTrack" to improve restroom maintenance at UTHM Pagoh block A1 by enabling issue reporting, task tracking, and have high supervision. The methodology used was the Multimedia Development Life Cycle (MDLC), which included stages like Concept, Design, Material Gathering, Assembly, Testing, and Distribution. The application was created with Android Studio using Java and using backed by Firebase Realtime Database for operative data management. 10 selective users were tested to show improved response time, better task organization and high user satisfaction. Through key associations, SparkTrack offers a solution to UTHM pagoh campus regarding hygiene issues by enhancing accountability, efficiency, and sustainability through mobile application technology.